Screening of in vitro and in silico α-amylase, α-glucosidase, and lipase inhibitory activity of oxyprenylated natural compounds and semisynthetic derivatives. (July 2021) - Faraone, Immacolata; Russo, Daniela; Genovese, Salvatore; Milella, Luigi; Monné, Magnus; Epifano, Francesco; Fiorito, Serena
Abstract: Metabolic syndrome has several characteristic manifestations, including insulin resistance and dyslipidaemia, that demand therapeutic approaches, such as the inhibition of enzymes involved in nutrient absorption and digestion.This study aimed to evaluate the potential pharmacological use of natural compounds widespread in the plant kingdom and their semisynthetic compounds against target enzymes. Twenty-three oxyprenylated natural compoundswere investigated for their ability to inhibit α -amylase, α -glucosidase, and pancreatic lipase enzymes by in vitro assays. Moreover, in silico molecular docking was performed to analyse their binding capabilities into 3D structures. Farnesyloxyferulic acid, geranyloxyvanillic acid, nelumal A, and geranyloxyferulic acid showed the highest inhibition activity in all three in vitro enzyme assays. Moreover, in silico molecular docking of these four compounds was used to analyse their possible binding in 3D structures of the investigated enzymes. The results indicate that these compounds have considerable therapeutic potential for the treatment of metabolic syndrome, and further studies are warranted for their pharmacological development. Graphical abstract: Natural and semisynthetic compounds effective vs α -amylase, α -glucosidase, and lipase. Image 1 Highlights: Natural compounds widespread in the plant kingdom and their derivatives. Inhibition of enzymes involved in postprandial hyperglycemia and lipid metabolism. In silico molecular docking to analyse the interaction in 3D-structures of enzymes. Best activity in in vitro enzyme assays by compounds with isoprenoid chains. Therapeutic potential use in metabolic syndrome by some investigated compounds.